2016
DOI: 10.5812/traumamon.31382
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Hospital Emergency in Iran: A Systematic Review

Abstract: ContextPre-hospital care plays a vital role in saving trauma patients.ObjectivesThis study aims to review studies conducted on the pre-hospital emergency status in Iran.Data SourcesData were sourced from Iranian electronic databases, including SID, IranMedex, IranDoc, Magiran, and non-Iranian electronic databases, such as Medline, Embase, Cochrane Library, Scopus, and Google Scholar. In addition, available data and statistics for the country were used.Data SelectionAll Persian-language articles published in Ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 32 publications
(44 reference statements)
1
22
0
Order By: Relevance
“…In addition, it is regarded as one of the most important issues in the world and has been presented as a measurable scale of treatment outcomes over the last few decades6 so that this assessment can be part of the treatment evaluation. The fertility status and its related factors lead to a change in the quality of life by inducing mental stress 67. In fact, the quality of life is a feeling of goodness and results from the satisfaction or dissatisfaction of various aspects of life which are important to the person 89.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is regarded as one of the most important issues in the world and has been presented as a measurable scale of treatment outcomes over the last few decades6 so that this assessment can be part of the treatment evaluation. The fertility status and its related factors lead to a change in the quality of life by inducing mental stress 67. In fact, the quality of life is a feeling of goodness and results from the satisfaction or dissatisfaction of various aspects of life which are important to the person 89.…”
Section: Introductionmentioning
confidence: 99%
“…A contentment of the services provided by EMS can have a significant impact on the total satisfaction of patients about healthcare systems (10). Nowadays, a growing importance is being attached to ambulances for the timely transfer of patients to medical centers as the availability of equipped ambulances in emergency situations can play the most important role in saving the patients' life and reducing the subsequent casualties (11). Kuisma et al suggested that patients' dissatisfaction increases when they are not transferred to their desired hospital.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main strategies to reduce the burden of injuries, especially caused by RTIs, is investing on and developing Prehospital Emergency Care (PEC) [7][8][9]. PEC ranged from a patient's bedside in the community to a hospital emergency [10]. Quick, efficient, and effective PEC can save the lives of many patients at vital moments [11].…”
Section: Introductionmentioning
confidence: 99%